Effect of inside-outside school alternated teaching units on knowledge of the environment for physical conditioning and related psychological outcomes in the Physical Education setting: A cluster-randomized controlled trial - Santiago Guijarro-Romero (Asociación Española de Ciencias del Deporte, 2024)
The main aim of the present study was to examine the effect of two inside-outside alternated teaching units on students' environmental knowledge for physical conditioning outside of school, their perceptions of barriers, autonomy support, motivation towards physical activity, intention to be physically active, their habitual and extracurricular physical activity, and the regular use of their environment for practicing physical activity. One hundred and forty-six high school students (50% females) aged 11-15 years old participated in the study. Six pre-established classes, balanced by grade, were cluster-randomly assigned into the alternated group (n = 75) or traditional group (n = 71). The alternated group students performed two fitness-based teaching units twice a week for four weeks, alternating lessons inside and outside the school. Meanwhile, the traditional group students performed a fitness teaching unit solely having lessons inside the school center. All variables were measured before and after the intervention by validated questionnaires. The Multilevel Linear Model showed that the alternated teaching units improved students' knowledge of their environment for physical conditioning, autonomy support, and autonomous motivation toward physical activity (p < 0.05; d = 0.16-1.30), while the rest of variables were not affected (p > 0.05). A four-week inside-outside school alternated teaching units improve students' key predisposition variables of habitual physical activity, but not the practice in itself. Some ideas are discussed in order to improve future Physical Education programs.